Socialization Of The Manufacture Of Ecobrick As A Solution To Management Of Plastic Waste In Nagari Tanjung Betung, Pasaman - Syukri, Daimon; Fauziah, Annisa (Andalasian International Journal of Social and Entrepreneurial Development, 2022)
The theme of Waste Processing Activities with Ecobrick The problem of plastic waste management in Nagari Tanjung Betung is still an unresolved problem. The absence of a landfill makes the people in the Nagari Tanjung Betung tend to litter on vacant land/land and also on the banks of rivers. In addition, many people in Nagari Tanjung Betung still use river water in their daily lives, be it for washing, bathing, defecating and urinating, and other activities. This poor sanitation will certainly trigger various diseases that can threaten the public's health status. Until now, conventional processing, such as dumping it in landfills or burning, has not been able to cope with the growing amount of plastic waste. Solution Along with the times and science, a solution is offered for managing plastic waste which is considered more effective, namely converting it into ecobricks. Ecobrick is an environmentally friendly brick made from plastic bottle waste filled with leftover plastic waste that is no longer used. The size of the plastic bottles used are free as available. Plastic bottles are filled with unused scraps of plastic waste so that there is no space left in the bottle nor is there any air left in the bottle so that the ecobrick doesn't slosh. Purpose The aim of waste management with ecobrick is to reduce waste scattered around the Nagari Tanjung Betung environment. The benefits of ecobricking are useful for more effective waste management so that later it will be able to make the environment cleaner and healthier. Besides being useful for waste management, the function of ecobricks can also be seen from an economic and functional perspective. Ecobricks can be a source of income if managed properly because the ecobricks themselves can be used as basic materials for making furniture, furnishings, and building materials such as the walls of a room. In addition to saving the cost of making these products, ecobricks can also be traded on the market with the same purpose as above. Methods and Stages of Implementation The methods and stages of implementing this activity start from licensing activities, identification and problem solving, preparation of tools and materials, ecobrick counseling. Results and Outcomes (Prototypes and/or Products) “Eco” and “brick” means environmentally friendly bricks. Called "brick" because it can be an alternative to conventional bricks in constructing buildings. Therefore, ecobrick is usually used as a raw material for making furniture. An ecobrick is a plastic bottle filled densely with non-biological waste to make reusable building blocks. Processing waste with Ecobrick will later be able to provide many benefits and benefits for the community. Conclusions and Suggestions Management of plastic waste in Nagari Tanjung Betung is still an unresolved problem. As the times progress, a solution for managing plastic waste is offered which is considered more effective, namely turning it into ecobricks. Ecobrick is an environmentally friendly brick made from plastic bottle waste filled with leftover plastic waste that is no longer used. It takes the desire and willingness of the community to directly contribute and change attitudes to no longer litter.